Providing comprehensive psychosocial care for adolescents with keloids in dermatology practice - Miner, Kaitlyn; Marciano, Rachel; Pugliese, Andrew; Kakarla, Sriya; Berman, Jacquelyn; Gonzalez, Karen; Frasier, Kelly; Mensah, Belinda; Vinagolu-Baur, Julia (International Journal of Research in Dermatology, 2025)
Keloids, characterized by excessive collagen deposition resulting in raised and often painful scars, profoundly affect the psychosocial well-being of adolescents, leading to anxiety, depression, and social withdrawal during a critical period of identity formation. Current literature highlights these challenges but lacks comprehensive management strategies within dermatological practice. This review identifies the need for integrated care models that combine clinical treatment with mental health support, including routine psychosocial screening, immediate counseling referrals, and adolescent-specific education programs on keloid management and emotional coping. Training dermatologists to recognize psychological distress and adopt compassionate communication is essential. Collaborative research should focus on evaluating these integrative care models and developing evidence-based guidelines. By pioneering these comprehensive strategies, dermatology practices can improve physical outcomes and significantly enhance the quality of life for adolescents with keloids, addressing both the physical and psychological scars. Future research should prioritize the longitudinal impact of these interventions on mental health and treatment adherence, establishing a new standard of care that fully supports adolescent keloid patients. By implementing these comprehensive strategies, dermatology practices can enhance physical outcomes and significantly improve the quality of life for adolescents with keloids, addressing both the physical and psychological impacts in the management of keloids in this vulnerable population.